Climate change in the Northern Rivers Catchment - New South Wales; New South Wales. Department of Environment and Climate Change; CSIRO ([Sydney, N.S.W.?] : [NSW Dept. of Environment and Climate Change?], 2007)
"This brochure has been prepared by the CSIRO to provide information about climate change and its consequences to landowners, landusers and the general public within the Northern Rivers Catchment."--Website of NSW Dept. of Environment and Climate Change.
Title from title screen (viewed on 7 March 2008).
Includes bibliographical references.
Text and graphics.
Mode of access: Internet via World Wide Web. On 7/03/2008 available from website of NSW Dept. of Environment and Climate Change at: http://www.greenhouse.nsw.gov.au/climate_change_in_nsw/climate_change_in_nsw_links
System requirements: Adobe Acrobat reader to view pdf file
Selected for archiving
Keywords: Climatic changes -- New South Wales -- Northern Rivers Region; Watersheds -- New South Wales -- Northern Rivers Region -- Environmental conditions; Northern Rivers Region (N.S.W.) -- Environmental conditions